2004
DOI: 10.1521/scpq.19.4.327.53504
|View full text |Cite
|
Sign up to set email alerts
|

The Perceptions of Academic Women in School Psychology: A National Survey.

Abstract: There is a paucity of research examining the experiences and perceptions of women employed as school psychology academicians. The purpose of this investigation was to ascertain female school psychology academicians’ perceptions of their respective academic climates, levels of support, incidences of harassment, and levels of stress. Comparisons between women currently working in psychology departments and those in colleges of education were of particular interest. A total of 128 female school psychology academi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 6 publications
1
12
0
Order By: Relevance
“…School psychology, like psychology as a whole, has increasingly been dominated by women (Akin- Little, Bray, Eckert, & Kehle, 2004). Curtis, Lopez, Castillo, Batsch, Minch, and Smith (2008) reported that 74% of NASP members are female.…”
Section: Discussionmentioning
confidence: 99%
“…School psychology, like psychology as a whole, has increasingly been dominated by women (Akin- Little, Bray, Eckert, & Kehle, 2004). Curtis, Lopez, Castillo, Batsch, Minch, and Smith (2008) reported that 74% of NASP members are female.…”
Section: Discussionmentioning
confidence: 99%
“…This final limitation suggests that it would be beneficial for the survey to be administered to male and female faculty simultaneously, which is the plan of the current authors. Importantly, however, simultaneous administration was not conducted with the data reported in this study, as the original goal was to survey women only (see Akin-Little et al, 2004). Akin- Little and colleagues (2004) designed their survey to meet the needs described by Fouad et al (2000) to better understand the perceptions and experiences of women in school psychology academia.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the experiences of academic school psychologists are sparse, and studies on the perceptions of academicians in school psychology as a function of gender are even rarer (Akin- Little, Bray, Eckert, & Kehle, 2004). School psychology, like psychology as a whole, is dominated by women.…”
mentioning
confidence: 99%
“…These data raise questions about differences in work climate. Akin- Little, Bray, Eckert, and Kehle (2004) surveyed female academic school psychologists and reported the positive finding that a majority (60.8%) did not believe that gender differences existed in their academic settings. However, when asked to judge whether particular aspects of the academic climate favored men or women, respondents identified factors, including salary and the amount of respectful interactions, as favoring men.…”
Section: Future Researchmentioning
confidence: 99%